New Onset Granulomatosis with Polyangiitis Associated with COVID-19 - Moshe Y. Bressler; Naeha Pathak; Kelly Cervellione; Farshad Bagheri; Edward Epstein; Adnan Mir; Rebecca Tamez (Case Reports in Dermatological Medicine)
The coronavirus disease 2019 (COVID-19) has recently been found to cause cutaneous vasculitis in patients. Granulomatosis with polyangiitis (GPA) is a type of small and medium vessel vasculitis that is often associated with pulmonary issues and has been shown to raise diagnostic complications in COVID-19 infection. In this report, we discuss the first case of new-onset GPA in the setting of active COVID-19 infection. Symptoms often overlap between the two diseases, and while there is no current cure for COVID-19, rapid immunosuppressive initiation can be lifesaving for patients with GPA. Thus, this case is essential in expanding our current knowledge of COVID-19 and its many skin manifestations.